Highly efficient silencing of microRNA by heteroduplex oligonucleotides. Issue 14 (19th June 2019) - Yoshioka, Kotaro; Kunieda, Taiki; Asami, Yutaro; Guo, Huijia; Miyata, Haruka; Yoshida-Tanaka, Kie; Sujino, Yumiko; Piao, Wenying; Kuwahara, Hiroya; Nishina, Kazutaka; Hara, Rintaro Iwata; Nagata, Tetsuya; et al.
Abstract: AntimiR is an antisense oligonucleotide that has been developed to silence microRNA (miRNA) for the treatment of intractable diseases. Enhancement of its in vivo efficacy and improvement of its toxicity are highly desirable but remain challenging. We here design heteroduplex oligonucleotide (HDO)-antimiR as a new technology comprising an antimiR and its complementary RNA. HDO-antimiR binds targeted miRNA in vivo more efficiently by 12-fold than the parent single-stranded antimiR. HDO-antimiR also produced enhanced phenotypic effects in mice with upregulated expression of miRNA-targeting messenger RNAs. In addition, we demonstrated that the enhanced potency of HDO-antimiR was not explained by its bio-stability or delivery to the targeted cell, but reflected an improved intracellular potency. Our findings provide new insights into biology of miRNA silencing by double-stranded oligonucleotides and support the in vivo potential of this technology based on a new class of for the treatment of miRNA-related diseases.